L’introduzione dell’insulto nel dibattito su Heidegger: Thomas Sheehan: In memoriam Johannes Fritsche (1949-2020) - Faye, Emmanuel (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2022)
Thomas Sheehan’s attack on my book Heidegger, The Introduction of Nazism into Philosophy in Light of the Unpublished Seminars of 1933-1935, published in “Philosophy Today” under the title”, addresses neither the book’s topic nor its arguments. He instead highlights a few isolated details in a sophistic and biased fashion. Moreover, his exposition is interspersed with ad personam insults not typically found in philosophical or scientific discussions, such as mocking the supposed “crass ignorance” of his opponent or even, in a second article, his alleged “cretinous readings” and portraying him as a possible “fraud”, a term that is tantamount to defamation and would warrant legal action. Sheehan (qui c’è uno spazio di troppo) remediated his attack, which was rolled out at the end of a colloquium on Heidegger’s Black Notebooks in New York. He obviously had not read the Notebooks and had nothing to say about them, undoubtedly because they would have fundamentally challenged his own watered-down interpretation of the Heideggerian corpus. He thus had to create a diversion, in defiance of the most basic rules of academic exchange, as both Sidonie Kellerer and Richard Wolin pointed out at the time. The essential points of Sheehan’s critique were precisely and carefully refuted after the publication of his article by Johannes Fritsche and others. Although up to now I had been resolved not to respond to personal attacks, taking the insults of a virulent Heideggerian as a compliment to critique – one insults only what one cannot refute – I owe it to the memory of the recently deceased Professor Fritsche to take my turn to speak and to thereby pay intellectual tribute to him. Heidegger; Dasein; Bodenständigkeit.